Rise of the far right technologies of recruitment and mobilization - Bessant, Judith; Watts, Rob; Devries, Melody (Rowman & Littlefield, 2021)
"This edited collection offers readers a practical focus on how media technologies are involved in recruitment and mobilization processes of far-right groups"--